HUBUNGAN PAPARAN PORNOGRAFI MELALUI MEDIA SOSIAL INTERNET TERHADAP MOTIVASI BELAJAR MAHASISWA - Yoga Saputra; Suryani Suryani; Bayu Azhar (STIKes Al-Insyirah Pekanbaru, 2020)
Motivation has a very big role in learning outcomes. Motivation can foster student interest in learning. Students who have high learning motivation tend to have a positive attitude to succeed. The research objective was to see the relationship between exposure to pornography through internet social media on learning motivation Probability taking technique. The research design used was a free description of the cross sectional design. Collecting data using a research instrument in the form of a questionnaire that has been tested for validity with the results obtained r table of 0.25. The analysis used was the frequency distribution and chi-square statistical test. The results of the study concluded that there was no relationship between exposure to pornography through social media on learning motivation p value = 0.896. For further researchers, the results of this study can be used as a medium of information and increase knowledge about exposure to pornography through social media on learning motivation.